Efficiency or Innovation? Competitive Strategies and Bankruptcy Risk in Indonesia’s Textile Industry - Qurrotul Aini; Heru Tjaraka (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the effectiveness of cost leadership and product differentiation strategies in reducing bankruptcy risk among labor-intensive textile and textile product firms in Indonesia. It also analyzes the moderating role of firm size in these relationships.Method: This study adopts a quantitative approach using secondary data derived from the financial reports of textile companies listed on the Indonesia Stock Exchange during the 2014–2024 observation period.Result: The findings indicate that both cost leadership and product differentiation strategies significantly reduce bankruptcy risk, suggesting that efficiency-based and innovation-oriented strategies enhance firms’ financial stability. Firm size strengthens the effect of cost leadership on the reduction of bankruptcy risk, implying that larger firms benefit from scale advantages. However, firm size does not significantly moderate the relationship between product differentiation and bankruptcy risk.Practical Implications for Economic Growth and Development: This study provides valuable insights for managers and policymakers in formulating competitive strategies that enhance firm survival and financial resilience in the labor-intensive textile industry. By reducing bankruptcy risk, effective strategic choices may contribute to employment stability, industrial sustainability, and long-term economic growth in developing economies such as Indonesia.Originality/Value: This study offers new empirical evidence by comparing the effects of cost leadership and product differentiation strategies on bankruptcy risk and by examining the moderating role of firm size in Indonesia’s labor-intensive textile industry, an area that has received limited attention in previous research.